A Green Enzymatic Extraction Optimization and Oxidative Stability of Krill Oil from Euphausia Superba - Li Zhou; Fu Yang; Minghao Zhang; Jikai Liu (Marine Drugs, 2020)
Krill oil enriched with polyunsaturated fatty acids is in the form of phospholipid. However, its application as a dietary supplement is limited, because of its rapid deterioration. Thus, this study aims to investigate the oxidative stability of krill oil extracted from Euphausia superba. Under optimal conditions (enzyme concentration 0.16%, enzymolysis time 2.9 h, and enzymolysis temperature of 45 °C) designed by response surface methodology, the extraction yield of krill oil is 86.02%. Five assays, including peroxide value (POV), thiobarbituric acid-reactive substances (TBARS), pH value, and turbidity were used to determine the oxidative stability of krill oil nanoliposomes during storage. Carboxymethyl chitosan (CMCS) nanoliposomes showed a significant reduction in POV and TBARS values, a prevention of pH value decrease and turbidity increase. This study indicated that CMCS nanoliposome can effectively improve the oxidative stability of krill oil during storage. Furthermore, the release profile in vitro illustrated that the controlled release of krill oil carried out by CMCS nanoliposomes is feasible.